The accountability paradox of the financial services authority following Law Number 4 of 2023: Between strengthened capital market supervisory powers and the elimination of public access to administrative courts - Adi Suranta Ginting; Faryanti Tjandra; Yuni Eliani; Gilbert Marcelino Hasudungan Gultom; Sebastianus Maryono; Novalia Andriati Br Hombing Lbt; Paltiada Saragi (PT Wim Solusi Prima, 2026)
Law Number 4 of 2023 on Financial Sector Development and Strengthening (P2SK Law) constitutes the most comprehensive financial law reform in Indonesian history. While significantly expanding the authority of the Financial Services Authority (OJK) over capital market supervision, the law simultaneously creates a profound accountability paradox: Article 45A establishes that all OJK decisions and actions are exempt from judicial review by the State Administrative Court (PTUN). This article examines the paradox through three research questions: first, whether Article 45A contravenes the principle of due process of law and the General Principles of Good Governance (AAUPB); second, whether the newly established OJK Supervisory Board can adequately substitute the removed PTUN access; and third, what constitutes an ideal accountability mechanism for OJK consistent with good governance principles without compromising investor protection in capital markets. Employing normative legal research with statutory, conceptual, and case approaches, this article finds that the closure of PTUN access violates the rule of law principle enshrined in Article 1(3) of the 1945 Constitution. The OJK Supervisory Board in its current form is insufficient as a substitute. This article recommends transforming the OJK Supervisory Board into an independent quasi-judicial tribunal as a short-term priority, with selective restoration of PTUN access as a long-term measure.